Pengaruh Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Hasil Belajar Kognitif dan Sikap Ilmiah Siswa Kelas V Muatan Pelajaran IPA - Omega Oktavia Rizana; Endang Widi Winarni; Irwan Koto (UNIB Press, 2023)
The research aims to determine the effect of the Snowball Throwing cooperative learning model on cognitive learning outcomes. This research is a quantitative research with a quasi-experimental design method. The population of this study were students in class VA and VB, which consisted of 60 students. Data collection techniques in this study are through documentation, questionnaires, observation, questionnaires and tests. The test used to measure students' cognitive learning outcomes is in the form of multiple choice questions totaling 20 items related to the content of the Natural Sciences lesson, theme 7, material changes in the form of objects. Questionnaires were given to students to assess students' scientific attitudes from the dimensions of being curious and open-minded in the form of positive and negative statements as many as 15 statements. The results showed that the average cognitive learning outcomes of students at level 1 of knowledge, cognitive learning outcomes of students at level 2 of application or application, and cognitive learning outcomes of students at level 3 of scientific reasoning and attitudes of students in the dimension of curiosity using the Snowball Throwing cooperative learning model in Science learning in general is very good. The N-Gain test from the pretest and posttest results of cognitive learning and scientific attitude is included in the medium category. Based on the results of the research and discussion, it was concluded that there was an influence of the Snowball Throwing type of cooperative learning model on students' cognitive learning outcomes and scientific attitudes of fifth grade students at SDN 06 Ujan Mas, science content.